Phase Change and Corrosion Effect on the Performance of a High Voltage Transmission Conductor - Khan, A.A; Rigit, A.R.H.; Bong, D.B.L (ENCON 2013, 2013)
High voltage transmission conductors used worldwide are produced in several configurations. One such configuration is composed of 26 aluminum spiral shaped strands placed at the outer ring and 7 steel strands which are supposed to hold the weight of the conductor, at the inside of the aluminium strands. The present work investigates the effect of time, temperature fluctuations and weather on the properties of such a conductor, over a long period of time (over 25 years). The temperature and load fluctuations create stresses due to expansion and contraction and the protective coating disintegrates due to the friction between the surfaces of the strands. It is also observed that a gradual reduction in diameter exists approaching the failure point which is attributed to the third stage of creep. X ray studies reveal oxidation and a change in grain size which supports the existence of creep. The conductor performance is deteriorated due to a combined effect of corrosion, disintegration of protective coating, reduction in diameter, increase in temperature due to high load and the resulting thermal stresses.